2018
DOI: 10.4314/njp.v45i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Serum total protein and albumin levels among malnourished children aged 6- 59 months in Zaria

Abstract: Background: Children with PEM have greater deficiency of total protein and albumin and in severe cases the total protein may be reduced to about 50 percent. Objective: To determine the serum protein and albumin levels among children with Protein Energy Malnutrition and the controls at Institute of Child Health, Ahmadu Bello University Teaching Hospital (ABUTH) Zaria. Method: This study was a case control health-based descriptive study to estimate the prevalence of serum protein and serum albumin in undernouris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…9 Immune system disorders, gastrointestinal disorders, cardiovascular disorders, respiration disorders, neurology disorders, hematology disorders, and PEM accompanied by micronutrient deficiencies (calcium, phosphate and vitamins A, C, and D) can interfere with the odontogenesis process, increasing the risk of caries, delayed eruption, and impaired salivary glands. 11,26 The results showed that rats exposed chronically to AFB1 cause shorter body length compared with control rats. PEM conditions that occurred in the intervention rats were accompanied by decreased levels of total protein in the saliva, hormonal abnormalities, including decreased levels of PTHrP and decreased antibodies in salivary secretions (sIgA).…”
Section: Discussionmentioning
confidence: 97%
“…9 Immune system disorders, gastrointestinal disorders, cardiovascular disorders, respiration disorders, neurology disorders, hematology disorders, and PEM accompanied by micronutrient deficiencies (calcium, phosphate and vitamins A, C, and D) can interfere with the odontogenesis process, increasing the risk of caries, delayed eruption, and impaired salivary glands. 11,26 The results showed that rats exposed chronically to AFB1 cause shorter body length compared with control rats. PEM conditions that occurred in the intervention rats were accompanied by decreased levels of total protein in the saliva, hormonal abnormalities, including decreased levels of PTHrP and decreased antibodies in salivary secretions (sIgA).…”
Section: Discussionmentioning
confidence: 97%
“…This study found 47.8% hypoalbuminemia and 10.1% ketonuria. A study by Abdullahi found that 47.1% of malnourished children had hypoalbuminemia with a low serum total protein level of 49.2% compared to controls (Abdullahi et al, 2018). These low levels of total serum protein and albumin can be caused by protein deficiency that causes synthesis disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Acetoacetate and 3hydroxybutyrate are carried from the liver to the extrahepatic tissue, for example, through the blood circulation. Acetoacetic acid and 3-hydroxybutyric acid are medium strength acids that will be balanced if they are present in blood or tissues, however, if the two keton bodies are released continuously in large amounts, there will be ketonemia and ketonuria (Abdullahi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced intake of high-protein foods can decrease protein synthesis, leading to hypoalbuminemia. Hence, the hypoalbuminemia of undernourished preschool-aged children can be assessed in terms of their inadequate dietary protein intake [ 33 ]. All subjects who consumed orange almond potato cookies for 2 months in this study had adequate levels of protein and zinc intake (≥70% RDA).…”
Section: Discussionmentioning
confidence: 99%